THE INFLUENCE OF ORGANIZATIONAL CULTURE AND COMPENSATION ON EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS A MEDIATING VARIABLE AT THE SOUTH TAPANULI REGIONAL DISTRICT / CITY BPS - Fandi Kusuma; Sri Gustina Pane; Beby Karina Fawzeea Sembiring (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
PURPOSE - Strong organizational culture, which includes positive values, can increase employee motivation and engagement, which has implications for their performance. In addition, good compensation is expected to increase employee satisfaction and motivation. This study aims to determine the effect of organizational culture, compensation on employee performance with work motivation as an intervening variable at BPS Regency / City Regional Tapanuli Selatan.METHODOLOGY - .This type of research is quantitative. The number of samples in this study was 90 respondents, the data analysis techniques used in this study were instrument tests (validity tests and reliability tests) hypothesis tests (t-test and coefficient of determination) and research models of path analysis tests (Path Analysis).FINDING - The results of this study indicate that Organizational Culture has a positive and significant effect on Performance, Compensation has a positive and significant effect on Employee Performance, Work Motivation has a positive and significant effect on Employee Performance, Organizational Culture has an effect on through the Work Motivation variable and Compensation has an effect on Performance through the Work Motivation variable at BPS Regency / City Regional South Tapanuli